Effect of the pH in the formation of beta-galactosidase microparticles produced by a spray-drying process - Berta N. Estevinho (2015)
The objective of this work was to investigate the influence of pH in the microencapsulation process, using a modified chitos an to microencapsulate the enzyme beta-galactosidase, by a spray-drying technique. Structural analysis of the surface of the particles was performed by scanning electron microscopy (SEM), showing that the obtained microparticles have an average diameter smaller than 3.5 mu m and in general a regular shape. The activity of the enzyme was studied by spectrophotometric methods using the substrate P-nitrophenyl-beta,D-galactopyranoside (ONPG). The parameters of Michaelis-Menten were calculated. The value of K-m decreases with the decrease of the pH, which can be associated to an increase of the affinity between the enzyme and substrate to smaller pH's. The highest value of the parameter V-max, representing the maximum reaction rate at a given enzyme concentration, was obtained at pH 6.